Analisis Visualisasi Data Pengangguran Di Indonesia Tahun 2018-2024 Dengan Menggunakan Dashboard Tableau - Nur ELISKA (Jurnal Dinamika Informatika, 2026)
The unemployment is still a problem in Indonesia. Unemployment has an impact on society and the country. The unemployment rate has fluctuated from year to year, indicating that there is still no stability in this situation. Data from the Central Statistics Agency (BPS) shows that Indonesia still has an unresolved unemployment problem. The available data is so vast and complex that it poses a challenge in receiving this information. The method used is qualitative. Researchers need to visualize the data to see the distribution of unemployment rates in Indonesia. This data visualization uses a Tableau dashboard. Tableau is an interactive platform that aims to facilitate the delivery of information related to unemployment rates in a more practical, fast, and accurate manner. The highest unemployment rate occurred in 2020, then decreased in 2023 and increased again in 2024. The highest unemployment rate was in the West Java region. Thus, the use of a Tableau dashboard for such a large amount of data makes it easier to receive information and understand the unemployment rate in Indonesia, which aims to address this condition Keywords: Data Visualization, Unemployment of Indonesia, Tableau